Bandicam: Alternatif Media Pembelajaran Interaktif dan Komunikatif di Masa Pandemi Covid 19 - Pirman Ginting; Yenni Hasnah; Diani Syahputri (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2022)
This activity is Bandicam-based learning media workshop for teacher aims to elevate the competence of teachers in utilizing online learning media in order to create more interesting/interactive/communicative teaching and learning activities, particularly during the Covid 19 pandemic. In an effort to realize this goal, this activity is carried out in collaboration with partner schools through socialization method and workshop. Based on the results, the teachers reveal that this activity was very benefeted for them in enriching the insight and creativity of the teachers to apply more interesting and interactive learning media for online learning so that students would become more motivated and enthusiastic in participating in learning. It is indicated from the ability of teachers to produce learning videos that are quite interesting and communicative through the Bandicam application.